Investigation of the survival of bacteria under the influence of supporting electrolytes KCl , CuI and NaBr in the electrochemical method - Masoumeh Moghaddam-Arjmand; Maziar Naderi; Solmaz Gholami (Mashhad University of Medical Sciences, 2018)
Abstract Background and aims: Drinking water pollution is a serious threat for public water supply. Water disinfection has a very important role in the reduction of pathogenic microorganism. Water electrodisinfection is an efficient and cost-effective method in water disinfection. The aim of this study was the survey of inactivation in two types bacteria (as index and resistant) by electrochemical process in the presence of supporting electrolytes. Materials and methods:Inactivation of E.Coli and Bacillus subtilis spore was studied at current intensity of 500mA, with each of the supporting electrolytes including CuI, NaBr and KCl. The type of electrodes was steel and the distance between electrodes was 2cm. Furthermore, the tests carried out in monopolar mode Fe-Fe, neutral pH and experimental temperature (21o c). The number of bacteria, amount of supporting electrolyte, voltage, and electrochemical action time were investigated. Results:Adding the supporting electrolytes to the electrochemical disinfection process decreased bacterial resistan Copper iodide (CuI) on 2 mg/l concentration showed more efficiency  in bacterial inactivation. Conclusion:Supporting electrolyte CuI with concentration of 2 mg/l both enhances the electrochemical process performance due to an increase in ionic transmission rate and voltage current. Also, this decreases electrochemical inactivation time and increases bactericidal effect.